Pengelolaan Pembelajaran Anak Berkebutuhan KhususDi Sekolah Dasar Penyelenggara Pendidikan InklusifSekolah Dasar Negeri Iii Giriwono Wonogiri - SUPARDJO, SUPARDJO, Prof. Dr. Sutama, M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
This study aimed to describe: 1) the learning plan for children with special needs in inclusive primary school education providers, 2) the implementation of learning for children with special needs in inclusive primary school education providers, 3) evaluation of learning for children with special needs in inclusive primary school education providers. This research is qualitative descriptive type. Implementation of research on SDN III Giriwono Wonogiri. The technique of collecting data using interviews, observation, and documentation. Respondents of this research are principals, classroom teachers, special counselor teacher, visit teacher and teacher assistant, and head, of the committee. The results showed that: 1) Planning learning inclusive education at Public Elementary using applicable curriculum at public elementary schools, planning duplication, planning flexibility and planning a modified full or in part and special programs in accordance with the constraints and the ability of children with special needs. 2) Implementation of Inclusive education learning at Public Elementary with a classical system, special classes, class skill and the arts. Implementation of classical learning by classroom teachers using methods, strategies, and how to increase and decrease material that has been set out in the RPP and adapted to learning characteristics of children with special needs. Implementation of learning special classes for children with special needs in primary by Special Counselor Teacher (GPK) with a special program, and individual service in a special room, but not yet implemented every day learning for special counselor teachers was presented from the Special School (SLB ). Implementation of classroom learning skill and art by visit teacher who is also at present from another school. 3) Evaluation of Children with Special Needs Learning in Elementary includes assessing the attitudes, knowledge, and skills. Ratings attitude for children with special needs to follow the general assessment all students. Knowledge assessment carried out at normal child despite adjustments manner, matter or content adjustment means, and the time adjustment. In the assessment of knowledge is not in accordance with their competence level indicators of children with special needs in accordance inclusive education program, which is the same assessment of different abilities, should be different too. While the skills assessment carried out together with normal children with the same standard. Need to be socialized to the community that the school education together with the planning of the same, different implementation, and assessment is certainly different, but what happens when the assessment by default the same, it is necessary to increase knowledge of classroom teachers through education and training in planning, implementation, and assessment of learning exactly match the competency of children with special needs.